The Bahamas : Financial Sector Assessment Program-Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2019)
The Bank Supervision Department (BSD) of the Central Bank of the Bahamas (CBoB) has a generally effective supervisory program in place for the size and complexity of the Bahamian banking system. Since the prior FSAP in 2012, clear progress has been made enhancing the framework in a number of areas as well as in the execution of its supervision program. CBoB supervision continues to evolve in a number of positive directions, with most of the areas viewed by assessors as warranting enhancements included in the execution of the program.